Professional Teacher Development in Educational Organizations - I. Avdeeva, Tat’yana; I. Vysokos, Maria; I. Zykova, Svetlana; G. Kalinina , Irina (International Journal of Psychosocial Rehabilitation, 2020)
The paper considers the theoretical integration and professional practical development for teachers in educational organizations by enhancing their pedagogical competence as part of advanced teacher training. The analysis resulted in comparative characteristics of key teacher competencies in different countries. Professional teacher development is only possible in the presence of teachers’ high level of self-awareness and motivation. The study revealed that, during the research process, the experimental group showed changes in the distribution of levels of teacher competence development. Statistical methods confirmed the reliability of the research results. Internal and external factors influencing teacher training in Russia were identified. Nation-specific peculiarities of Russian teacher behavior were described, in particular the intensive development of all competencies and quick access to the international arena. A comparative analysis of teacher competence development in different countries was made. The potential was investigated for improving the advanced teacher training system within and beyond educational organizations. A model for teacher development in educational organizations was developed.